2021
DOI: 10.3390/v13020342
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Cytokine Response in Neuroinvasive and Non-Neuroinvasive West Nile Virus Infection

Abstract: Data on the immune response to West Nile virus (WNV) are limited. We analyzed the antiviral cytokine response in serum and cerebrospinal fluid (CSF) samples of patients with WNV fever and WNV neuroinvasive disease using a multiplex bead-based assay for the simultaneous quantification of 13 human cytokines. The panel included cytokines associated with innate and early pro-inflammatory immune responses (TNF-α/IL-6), Th1 (IL-2/IFN-γ), Th2 (IL-4/IL-5/IL-9/IL-13), Th17 immune response (IL-17A/IL-17F/IL-21/IL-22) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, neurotropic/neuroinvasive WNV infection has been associated with altered blood-brain barrier (BBB) permeability with a subsequent release of IFN-γ and other proinflammatory cytokines ( 29 ). Accordingly, a recent observational clinical study demonstrated increased concentrations of the key anti-viral/proinflammatory cytokines interleukin-6 (IL-6) and IFN-γ in cerebrospinal fluid (CSF) samples of patients with neuroinvasive WNV infection ( 30 ). Finally, in a preclinical rodent model of recurrent neuroinvasive HSV-1 infection, expression of neuroinflammatory cytokines, such as IL-1β and IL-6, in the hippocampus of HSV-1 infected mice was correlated with an increased incidence of cognitive deficits ( 31 ).…”
Section: Infection Of the Brain: Chronicity Neuronal Activity And Cognitionmentioning
confidence: 99%
“…Furthermore, neurotropic/neuroinvasive WNV infection has been associated with altered blood-brain barrier (BBB) permeability with a subsequent release of IFN-γ and other proinflammatory cytokines ( 29 ). Accordingly, a recent observational clinical study demonstrated increased concentrations of the key anti-viral/proinflammatory cytokines interleukin-6 (IL-6) and IFN-γ in cerebrospinal fluid (CSF) samples of patients with neuroinvasive WNV infection ( 30 ). Finally, in a preclinical rodent model of recurrent neuroinvasive HSV-1 infection, expression of neuroinflammatory cytokines, such as IL-1β and IL-6, in the hippocampus of HSV-1 infected mice was correlated with an increased incidence of cognitive deficits ( 31 ).…”
Section: Infection Of the Brain: Chronicity Neuronal Activity And Cognitionmentioning
confidence: 99%
“…Recently, we described the expression patterns of cytokines in paired CSF and serum samples collected from 37 WNV NID patients after a median of 5 days since the onset of symptoms, and in the serum of patients with WNV fever. A well-defined pattern of cytokine expression that included a high intrathecal synthesis of IL-6; lack of significant differences in the serum vs. CSF concentrations of IL-13, IL-9, IL-10, IFN-γ, and IL-22; as well as by the absence of IL-2, IL-4, TNF-α, and Th17 cytokines in the CSF was observed [36]. The present study results, focusing specifically on severe WNV NID, have shown a consistent expression of IL-6 in the CSF and serum.…”
Section: Discussionmentioning
confidence: 88%
“…In the CSF, increased concentrations of the key cytokines associated with innate and early acute phase responses (IL-6) and Th1 type immune responses (IFN-γ) were found. In contrast, expression of the key T-cell growth factor IL-2, Th17 cytokines, a Th2 cytokine IL-4 and the proinflammatory cytokine TNF-α appeared to be concentrated mainly in the periphery [42].…”
Section: Wnv Infections In Humansmentioning
confidence: 84%